2014
DOI: 10.2337/db13-0991
|View full text |Cite
|
Sign up to set email alerts
|

Generation of L Cells in Mouse and Human Small Intestine Organoids

Abstract: Upon a nutrient challenge, L cells produce glucagon-like peptide 1 (GLP-1), a powerful stimulant of insulin release. Strategies to augment endogenous GLP-1 production include promoting L-cell differentiation and increasing L-cell number. Here we present a novel in vitro platform to generate functional L cells from three-dimensional cultures of mouse and human intestinal crypts. We show that short-chain fatty acids selectively increase the number of L cells, resulting in an elevation of GLP-1 release. This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 36 publications
3
95
0
1
Order By: Relevance
“…This indicates that the amplification of GLP-1 secretion was largely dependent on L cell mass and that DBZ treatment did not impair the glucose responsiveness of L cells. We next tested whether the effect of DBZ can be further amplified by SCFAs, which themselves increase L cell numbers in small intestinal organoids by approximately 2-fold (13). SCFAs increased the number of L cells in both DBZ-treated and control mouse organoids ( Figure 1F).…”
Section: Effect Of Notch Inhibition On Development Of Mouse and Humanmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the amplification of GLP-1 secretion was largely dependent on L cell mass and that DBZ treatment did not impair the glucose responsiveness of L cells. We next tested whether the effect of DBZ can be further amplified by SCFAs, which themselves increase L cell numbers in small intestinal organoids by approximately 2-fold (13). SCFAs increased the number of L cells in both DBZ-treated and control mouse organoids ( Figure 1F).…”
Section: Effect Of Notch Inhibition On Development Of Mouse and Humanmentioning
confidence: 99%
“…Finally, the expression of preproglucagon defines the identity of mature L cells, which constitute only 0.5% of intestinal epithelial cells. We have recently shown that short-chain fatty acids (SCFAs) selectively increase the number of L cells in the intestinal epithelium in vitro, followed by a corresponding increase in GLP-1 secretion (13). SCFAs are likely to act through late endocrine precursors by increasing Neurod1 expression (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic technologies have enabled isolation of primary L cell populations suitable for secretion and electrophysiological analyses (91), and stem cell-derived gut organoids, including those of human origin, herald considerable potential for generation of diverse enteroendocrine cell populations from different sites along the gastrointestinal tract (92). Remarkably, despite the theoretical potential of enhancing L cell secretion for the treatment of metabolic disorders (1), there has been scant progress in clinical development of GLP-1 secretagogues exhibiting sustained efficacy in both preclinical and clinical studies.…”
Section: The Physiology Of Glp-1 Actionmentioning
confidence: 99%
“…High expression of pluripotent markers was evident in E2055A, which showed deviations from ideal ESlike morphology within maintenance cultures. Regenerative medicine approaches may be more appropriate by direct differentiation of crypt stem cell enteroids [32,33] rather than iPSC. Overall, these data can help improve cost-effectiveness, and ease of differentiation from different reprogrammed cell lines, enabling HIO to become more commonly available to research labs in this field.…”
Section: Discussionmentioning
confidence: 99%